13.1k views
5 votes
Can someone explain to me how do I do this?

This is for AP Calculus ​

Can someone explain to me how do I do this? This is for AP Calculus ​-example-1

1 Answer

4 votes

1. As
x\to+\infty, the expression
x^3 will remain positive and veer off to positive infinity as well. The constant term and coefficient on
x^3 don't affect this result:


\displaystyle\lim_(x\to\infty)(0.25x^3+3)=\infty

In the opposite direction,
x\to-\infty means
x will be negative, so
x^3 will also be negative. Then


\displaystyle\lim_(x\to-\infty)(0.25x^3+3)=-\infty

2. As
x\to+\infty, the exponent
4x will also go to positive infinity, so that


\displaystyle\lim_(x\to\infty)2\cdot10^(4x)=\infty

In the opposite direction,
4x would veer off to negative infinity. Then


10^(4x)\to10^{\text{large negative number}}=\frac1{10^{\text{large positive number}}}

and as
x gets larger in magnitude, this would force the expression to converge to 0, so that


\displaystyle\lim_(x\to-\infty)2\cdot10^(4x)=0

User Axxis
by
5.1k points